Kidney transplantation from expanded criteria donors: an increased risk of urinary complications – the UriNary Complications Of Renal Transplant (UNyCORT) study. (31st August 2021) - Mesnard, Benoit; Leroy, Maxime; Hunter, James; Kervella, Delphine; Timsit, Marc‐Olivier; Badet, Lionel; Glemain, Pascal; Morelon, Emmanuel; Buron, Fanny; Le Quintrec‐Donnette, Moglie; Pernin, Vincent; Ladriere, Marc; et al.
Abstract : Objectives: To assess the impact of expanded criteria donors (ECD) on urinary complications in kidney transplantation. Patients and Methods: The UriNary Complications Of Renal Transplant (UNyCORT) is a cohort study based on the French prospective Données Informatisées et VAlidées en Transplantation/Computerized and VAlidated Data in Transplantation (DIVAT) cohort. Data were extracted between 1 January 2002 and 1 January 2018 with 1‐year minimum follow‐up, in relation to 44 pre‐ and postoperative variables. ECD status was included according to United Network for Organ Sharing (UNOS) definition. The primary outcome of the UNyCORT study was the association between the donor's ECD/standard criteria donors (SCD) status and urinary complications at 1 year in uni‐ and multivariate analysis. Sub‐group analysis, stratified analysis on ECD/SCD donor's status and transplant failure analysis were then conducted. Results: Between 1 January 2002 and 1 January 2018, 10 279 kidney transplants in adult recipients were recorded within the DIVAT network. A total of 8559 (83.4%) donors were deceased donors and 1699 (16.6%) were living donors (LD). Among donation after circulatory death (DCD) donors, 224 (2.85%) were uncontrolled DCD and 93 (1.09%) were controlled DCD donors. A total of 3617 (43.9%) deceased donors were ECD. The overall urological complication rate was 16.26%. The donor's ECD status was significantly associated with an increased risk of urological complications at 1 year in multivariate analysis (odds ratio: 1.50, 95% CI 1.31–1.71; P < 0.001) and especially with stenosis and ureteric fistulae at 1 year. There is no association with LD, uncontrolled and controlled DCD. The placement of an endo‐ureteric stent was beneficial in preventing urinary complications in all donors and particularly in ECD donors. Conclusion: The donor's ECD status is associated with a higher likelihood of stenosis and ureteric fistulae at 1 year. Recipients of grafts from ECD donors should probably be considered for closer urological monitoring and systematic preventive measures.